Trajectories of Body Mass Index from Young Adulthood to Middle Age among Canadian Men and Women. (21st December 2015) - Wang, Meng; Yi, Yanqing; Roebothan, Barbara; Colbourne, Jennifer; Maddalena, Victor; Wang, Peizhong Peter; Sun, Guang
Abstract : Knowledge regarding the heterogeneity of BMI trajectories is limited for the Canadian population. Using latent class growth modelling, four distinct BMI trajectories of individuals from young adulthood to middle age were identified for both women and men from the longitudinal data of the National Population Health Survey. The associations between BMI trajectories and the individuals' sociodemographic characteristics and behavioural factors were also examined. Aboriginal women were found more likely to be in the long-term overweight or obese groups. It reveals that increased years of smoking, drinking, and being physically active were associated with lowering the BMI trajectory in all groups for both women and men, with some exceptions in the long-term normal weight group for men. Increased years of rural living, being employed, and living with low income were associated with raising the BMI trajectory in all groups for women and in some groups for men. Food insecurity was associated with raising the BMI trajectory in each group for both women and men.